Analysis of Physical Workload and Work Fatigue Among Irrigation and Fertilization Workers using Physiological Methods and the Swedish Occupational Fatigue Index - Saputri, Juwa; Erliana, Cut Ita; Bakhtiar, Bakhtiar (Newinera Publisher, 2025)
in completing tasks. High workloads can lead to increased fatigue among workers at PT. Simpang Kiri Plantation Indonesia, which operates in the palm oil plantation sector. This study aims to analyze the level of fatigue experienced by workers involved in loading Fresh Fruit Bunches (FFB) using physiological methods and the Swedish Occupational Fatigue Index (SOFI).Workers are required to perform under demanding physical conditions, with an average lifting load of 15-30 kg per load. The analysis results indicate that the workers' fatigue level falls within the moderate category, with a percentage of 100%. The highest dimension of fatigue is found in sleepiness, with a score of 10, followed by physical exertion with a score of 6.5. Additionally, lack of motivation and physical discomfort each have scores of 6.5 and 5.8, respectively, while lack of energy is recorded at the lowest value of 5.5.These findings provide important insights for improving work techniques and managing workloads within the company, as well as serving as a reference for further research aimed at reducing work fatigue.